2020
DOI: 10.3390/biom10071066
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Bioinformatic Investigations of Heat-Treated Anisakis simplex Third-Stage Larvae

Abstract: Anisakis simplex third-stage larvae are the main source of hidden allergens in marine fish products. Some Anisakis allergens are thermostable and, even highly processed, could cause hypersensitivity reactions. However, Anisakis proteome has not been studied under autoclaving conditions of 121 °C for 60 min, which is an important process in the food industry. The aim of the study was the identification and characterization of allergens, potential allergens, and other proteins of heat-treated A. simplex larvae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 96 publications
2
9
0
Order By: Relevance
“…However, SDS-PAGE and WB band profiles of Anisakis antigen after heating were clearly visible. Similar observations regarding the reduction of the number and intensity of bands in electrophoretic and WB profiles of autoclaved Anisakis antigen was reported in a previous study [ 34 ]. In the present investigation, we found that the heated antigen retained the ability to bind IgG antibodies and, therefore, it was possible to use them in CL-ELISA tests.…”
Section: Discussionsupporting
confidence: 90%
“…However, SDS-PAGE and WB band profiles of Anisakis antigen after heating were clearly visible. Similar observations regarding the reduction of the number and intensity of bands in electrophoretic and WB profiles of autoclaved Anisakis antigen was reported in a previous study [ 34 ]. In the present investigation, we found that the heated antigen retained the ability to bind IgG antibodies and, therefore, it was possible to use them in CL-ELISA tests.…”
Section: Discussionsupporting
confidence: 90%
“…This study is the first global proteomic analysis of the A. simplex (s.s.) L3 larval secretome. Previous proteomic investigations of Anisakis did not include profiling of the secretome proteins [13,[31][32][33][34][35][36][37][38]. Therefore, knowledge on A. simplex ES proteins is very fragmented, although important aspects related to metabolism, pathogenicity, and hostparasite interactions are known to be associated with ES proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Of the seven A. simplex ES allergens listed by WHO/IUIS [89], only Ani s 4 was detected in the present study. Ani s 4 is significant because of its heat-and pepsin-resistant properties and its ability to cause anaphylaxis [13,90,91]. Other Anisakis allergens were presumably not expressed in the in vitro culture conditions, or their concentration was below the limit of detection of LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the peptides were filtered at e-value < 0.05 for the false discovery rate (FDR) using the Mascot searching engine; that is to say, the ion scores were higher than corresponding identity scores 57,58 . The manual method and the PepEx (https://github.com/ eparker05/Pepti-deExtractor) were both used to map the distribution of peptides onto their full-length conopeptide protein sequences.…”
Section: Peptide Identificationmentioning
confidence: 99%